EFEK EKSTRAK DAUN MENGKUDU (Morinda citrifolia L.) TERHADAP JUMLAH PROTEIN GLUT4 PADA TIKUS PUTIH HIPERGLIKEMIK - Kirtishanti, Aguslina; Budiono, Ryanto; Ratih, .; Isfandiari, Fitria (Indonesian Research Gateway)
Difficulties in finding anti-diabetics which are effective, tolerable by the patients, safe, cause people to try to find other alternative, such as taking traditional medicine like “mengkudu” [Morinda citrifolia L.]. Mengkudu fruit had been proven to be able to increase the number of protein GLUT4 at type 2 diabetic male white rat’s sceletal muscle. Fruit of mengkudu has similar chemical ingredient with its leaves. So far, however, mengkudu leaves had not been studied to increase the number of protein GLUT4 at sceletal muscle. This study use male white rats Wistar strain. Total number of white rats involved in this study were 40 rats which treated : 10 rats as negative control group [no treatment], 10 rats as positive control group and they are treated with exogen insulin 0,35 U per body weight three times daily for 10 days. The last 20 rats is divided into 2 groups with 10 rat for each group as first trial group and second trial group. The trial group are treated with exogen insulin and first trial group were given water extract of mengkudu leaves 7,5 g per body weight and second trial group were given alcohol extract of mengkudu leaves 1,8 g per body weight twice daily which were administered starting from the seventh to tenth day of exogen insulin administration. After ten days of administration, blood glucose level of all rats was measured and all rats were killed afterwards. The next step is sceletal muscle tissue processing to be painted immunohistochemistry to GLUT4. Conclusion of the result is water extract and alcohol extract of mengkudu leaves could not increase the number of protein GLUT4 at type 2 diabetic male white rats. ABSTRAK Kesulitan mendapatkan obat antidiabetes yang efektif dan aman menyebabkan pasien mencoba obat alternatif, misalnya dengan menggunakan obat tradisional “mengkudu” (Morinda citrifolia L.). Buah mengkudu telah terbukti dapat meningkatkan jumlah protein Glut4 pada otot rangka tikus putih jantan diabetik. Buah mengkudu memiliki kandungan kimia yang hampir sama dengan daunnya. Oleh sebab itu dalam penelitian ini dilakukan penelitian untuk mengetahui apakah daun mengkudu juga dapat meningkatkan jumlah protein Glut4 seperti buahnya. Dalam penelitian ini digunakan 40 tikus putih jantan strain Wistar yang dibagi menjadi 4 kelompok, yaitu kelompok kontrol negatif, kelompok kontrol positif yang diberi insulin eksogen 0,35 U per berat badan tiga kali sehari selama 10 hari, kelompok perlakuan pertama yang diberi ekstrak air daun mengkudu 7,5 g per kg berat badan, dan kelompok perlakuan kedua yang diberi ekstrak alkohol daun mengkudu 1,8 g per kg berat badan dua kali sehari mulai hari ke-7 sampai hari ke-10. Kadar gula darah diukur setelah hari ke-10. Jaringan otot rangka diambil dan dilakukan pewarnaan untuk melihat protein Glut4. Dari hasil penelitian yang diperoleh disimpulkan bahwa ekstrak air dan alkohol daun mengkudu tidak dapat meningkatkan jumlah protein Glut4 pada tikus putih jantan diabetik tipe 2.